Resposta imune de tilápias do Nilo (Oreochromis niloticus) vacinadas contra Streptococcus agalactiae - Marcusso, Paulo Fernandes [UNESP] (2014)
Streptococcal infection causes significant losses in intensive farmed of tilapia in Brazil and one of the solutions is the use of vaccines. Thus, this study assessed the humoral and cellular immune response to a vaccine against S. agalactiae; and to this end were used 425 Nile tilapia, O. niloticus (200 ± 25 g). Firstly, the relative percentage of survival (PRS) was determined to evaluate which portions of sonicate S. agalactiae (soluble or insoluble) would be more efficient. For this, four groups were formed (n=20), G1 – injected with PBS, G2- injected with PBS + adjuvant incomplete of Freund; G3- immunized with the soluble fraction + adjuvant incomplete of Freund; G4 - immunized with the insoluble fraction + adjuvant incomplete of Freund. 21 days after immunization, fish were challenged with homologous strains (LC50) resulting in a PRS 100, 50, and 16.7% to G4, G3, and G2, respectively. Based on these results, the insoluble fraction was used to evaluate the humoral immune response. Group 5 (G5) was injected with PBS (control) and Group 6 (G6) was immunized with the insoluble fraction + incomplete Freund's adjuvant, intracoelomic route. They were performed blood samples at 0; 7; 14; 21; 28; 35; 42; 60, and 90 days post-vaccination. The evaluation of immune response was made by direct agglutination test in microplaque. The results showed that the vaccinated group presented titration from 21th day, with maximal response at 60 days post vaccination. To assess the cellular component of the nonspecific inflammatory response elicited by vaccination, three groups were used (n = 63), G7 – injected with PBS, G8- injected with PBS + incomplete Freund's adjuvant, G9 - immunized with the insoluble fraction + incomplete Freund's adjuvant. All injections were performed in the swim bladder. Therefore, we collected exudates at 6, 24, and 48 hours post-stimulus. The exudate results showed ...